Vertical structure and interaction of ozone and fine particulate matter in spring at Nanjing, China: The role of aerosol's radiation feedback. (1st February 2020) - Qu, Yawei; Wang, Tijian; Wu, Hao; Shu, Lei; Li, Mengmeng; Chen, Pulong; Zhao, Ming; Li, Shu; Xie, Min; Zhuang, Bingliang; Liu, Jingxian; Han, Yong
Abstract: The vertical structure of ozone (O3 ) and fine particulate matter (FPM) as well as their interactions are important for understanding the atmospheric chemistry process and their impact on climate. Through a ground-based lidar observation during April 18th-May 22nd 2017 and surface measurement during March 1st-May 31st 2017, this study obtained the vertical distribution of O3 and aerosol extinction coefficient with their correlations during the springtime in the lower troposphere (LT) in Nanjing, eastern China. Surface average O3 and PM2.5 concentrations in spring were 39.89 ppb and 41.93 μg m −3 . O3 generally increased with height in the LT, while aerosol extinction coefficient decreased. The correlation between O3 and aerosol extinction coefficient was −0.32 at 300 m, and 0.34 at 1747.5 m. An on-line coupled model Weather Research and Forecasting with Chemistry (WRF-Chem) was used to analyze the effect of aerosol's radiation feedback on ozone. Aerosol reduced the surface downward shortwave radiation by −25.66 W m −2, and increased the upwelling shortwave radiation at the top of atmosphere by 3.19 W m −2 in urban Nanjing. The photolysis rate of NO2 and O 1 D were reduced by −1% and −0.7% near surface and increased by 0.3% and 0.2% at upper LT. Aerosol-included effect also led to a more stable planet boundary layer (PBL), with −0.24 °C and −0.05 m s −1 changes in temperature and wind speed at surface. However, the temperature and wind speed increased by 0.18 °C and 0.13 m s −1 at 1760 m, respectively. O3 decreased by −3.70% at surface and increased by 0.89% at 2870 m. This study showed that aerosol can affect ozone through altering photolysis rate and atmospheric stability. Aerosol's radiation feedback has a complex effect on the vertical structure of ozone, which leads to ozone decrease near the surface and increase above the aerosol layer. Highlights: The vertical structure and the correlation of O3 and PM2.5 were analyzed. O3 increases with height in the lower troposphere, while aerosol decreases. PM2.5 reduces surface O3 by reducing photolysis rate and increasing PBL stability. PM2.5 and O3 are positive correlated at higher altitudes.